Dying and Rising with Christ - Schweizer, Eduard (New Testament studies, 1967)
The relation of the so-called ‘mystical’ to the so-called ‘juridical’ aspect of Paul's theology has been frequently discussed. While Albert Schweitzer thought that the doctrine of justification by faith was no more than a ‘side-crater’ in the Pauline theology, Rudolf Bultmann considered the idea of a participation in the destiny of Christ a Gnostic influence not really fitting into the Pauline pattern of thought. This disagreement is not of merely historical interest; behind it lies the central theological problem of the significance of Jesus' life, death and resurrection for us today. Is this significance to be expressed in the categories of an example to be followed or a forerunner, who opens the way ahead for us, or are the categories of sacrificial or vicarious death more adequate? At first sight, the two patterns seem to contradict each other. According to the first, the believer dies with Christ; Christ's death becomes the believer's death; according to the second, Christ dies under the curse of divine judgement, lest the believer undergo this judgement. However, the first observation that we make in the Pauline texts is the coincidence of both lines in the same sentence: II Cor. v. 14: ‘One has died for all; therefore all have died’; I Thess. v. 10: ‘Christ died for us so that whether we wake or sleep we might live with him.’